2011
DOI: 10.1007/jhep05(2011)124
|View full text |Cite
|
Sign up to set email alerts
|

Eluding SUSY at every genus on stable closed string vacua

Abstract: In closed string vacua, ergodicity of unipotent flows provide a key for relating vacuum stability to the UV behavior of spectra and interactions. Infrared finiteness at all genera in perturbation theory can be rephrased in terms of cancelations involving only tree-level closed strings scattering amplitudes. This provides quantitative results on the allowed deviations from supersymmetry on perturbative stable vacua. From a mathematical perspective, diagrammatic relations involving closed string amplitudes sugge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Using this method it was shown that non-tachyonic string configurations are characterised by a spectrum of physical excitations that not only must enjoy asymptotic supersymmetry but actually, at very large mass, bosonic and fermionic states are bound to follow a universal oscillating pattern, whose frequencies are related to the non-trivial zeroes of the Riemann ζfunction. Similar studies have then been generalised to higher genus [22][23][24] where similar constraints on the interactions of physical states are expected to emerge.…”
Section: Introductionmentioning
confidence: 73%
“…Using this method it was shown that non-tachyonic string configurations are characterised by a spectrum of physical excitations that not only must enjoy asymptotic supersymmetry but actually, at very large mass, bosonic and fermionic states are bound to follow a universal oscillating pattern, whose frequencies are related to the non-trivial zeroes of the Riemann ζfunction. Similar studies have then been generalised to higher genus [22][23][24] where similar constraints on the interactions of physical states are expected to emerge.…”
Section: Introductionmentioning
confidence: 73%
“…Other attempts to use the Rankin-Selberg method to compute string amplitudes or probe the asymptotic density of string states include[14][15][16][17][18][19].…”
mentioning
confidence: 99%
“…The idea of applying Rankin-Selberg-type methods to compute one-loop modular integrals, albeit in a rather different way from[18], was first put forward in[19]. Steps towards extending them to higher genus were taken in[20].…”
mentioning
confidence: 99%